Anxiety, inhibitory control, physical activity, and internet addiction in Chinese adolescents: a moderated mediation model - Yang Liu; Yuan Jin; Jiawei Chen; Lianghao Zhu; Yongxiang Xiao; Lei Xu; Tiancheng Zhang (BMC, 2024)
Abstract Background Adolescents may have anxiety due to a series of events such as school work and social interaction. Improper handling of anxiety often leads to some negative consequences, such as Internet addiction. Therefore, this study further explored the relationship between anxiety and Internet addiction, as well as the mediating role of inhibitory control between the two, and also considered the moderating role of physical activity between anxiety and inhibitory control. Methods A total of 1607 adolescents, comprising 664 boys and 943 girls with an average age of 15.86 years (SD = 0.73), from Shandong, Shanxi, Hebei, and Hunan provinces completed a self-report survey on physical activity, anxiety, inhibitory control, and Internet addiction. Descriptive analysis, correlation analysis, and mediation test were conducted. Results The results revealed a significant positive correlation between anxiety and adolescent internet addiction (r = 0.413, p < 0.001), and a significant negative correlation with inhibitory control (r = -0.423, p < 0.001). Inhibitory control was found to be significantly positively correlated with physical exercise (r = 0.143, p < 0.001) and significantly negatively correlated with internet addiction (r = -0.368, p < 0.001). After controlling for demographic variables, anxiety significantly positively predicted Internet addiction (β = 0.311, p < 0.001) in adolescents, and it also indirectly predicted Internet addiction through inhibitory control (β = -0.231, p < 0.001). Physical activity significantly weakened the predictive effect of anxiety on inhibitory control (β = -0.092, p < 0.001). Conclusions This study further explored the issue of psychological mechanisms between anxiety and Internet addiction in adolescents, and added that physical activity alleviates the negative effects of anxiety on adolescents. Schools and families are encouraged to promote physical exercise among adolescents to alleviate the influence of negative emotions on their psychological and behavioral health.